Employee Management During Times of Organizational Change: Strategies for Overcoming Resistance and Work Stress - Asniwati Asniwati; A. Nurwahyu Jaelani Ramadhan (STIE Amkop Makassar, 2025)
This study investigates effective strategies for managing employee resistance and work-related stress during organizational change. The research addresses key challenges organizations face in managing change by exploring leadership, communication, employee wellness programs, and adaptive HR practices. This research adopts a Systematic Literature Review (SLR) approach to synthesize existing studies on employee management during organizational change. The study analyzes empirical evidence and theoretical frameworks to identify strategies that mitigate resistance and stress in organizational transitions. The study highlights the critical role of transformational leadership, transparent communication, and employee wellness programs in reducing resistance and managing work-related stress. It identifies how clear communication and inclusive leadership contribute to higher employee engagement and adaptability. The research also underscores the importance of HR practices, such as agile performance management and HR analytics, in supporting smooth transitions. The findings provide actionable recommendations for organizations to implement comprehensive strategies prioritizing employee well-being and engagement during change. Managers are encouraged to adopt transformational leadership, improve communication, and integrate wellness programs to reduce resistance and stress. Future research could further explore the impact of these strategies in various industries and the potential role of emerging technologies.